Captain Cook - MacLean, Alistair. 1922-1987. (Garden City, N.Y., Doubleday, 1972)
"Born in obscurity but gripped by a boundless passion for new horizons, James Cook had become at the time of his death in 1779 the greatest combination of seaman, explorer, navigator, and cartographer that the world had ever known. He still is. He had driven himself mercilessly, and his men likewise, and yet the surgeon's mate on the 'Resolution' was able to write: 'In every situation he stood unrivalled and alone; on him all eyes were turned; he was our leading star, which a its setting left us involved in darkness and despair'. "
Keywords: Cook, James, -- 1728-1779.; Seaman -- Biography; Explorer -- Biography; Navigator -- Biography